Catching the Flu from the United States Synchronisation and Transmission Mechanisms to the Euro Area - Mauro, Filippo di; Dees, Stephane; Lombardi, Marco J. (Palgrave Macmillan UK, 2010)
Looking at historical cross-country interactions, this book examines the role of the US in the world economy. Illustrating that US shocks tend to have a global nature and that Monetary Union only partially shelters the Euro area from its external environment, the US should fully assume its responsibility, minimizing shock transmission
Keywords: Macroeconomics; International economics; Regional economics; Spatial economics